STRATEGI PONDOK PESANTREN SEBAGAI NOUBEL INDUSTRY DALAM MENJAGA KEPERCAYAAN MASYARAKAT - Fathor Rozi; Tiara Nurul Annisa' (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2023)
The purpose of this research is to describe how the Nurul Jadid Islamic boarding school's strategy maintains public trust as a noble industry. This research was conducted with a qualitative approach with a descriptive type. The data collection technique used was interviews with the Bureau of Education, Bureau of Islamic Boarding Schools, regional heads of West and East Islamic boarding schools, as well as documentation. Data analysis was carried out through three steps, namely: (1) data reduction; (2) data exposure; and (3) drawing conclusions and verification. Data validity with source and technique triangulation process. The results show that the Nurul Jadid Islamic Boarding School has two main strategies, namely understudy with the trilogy of students and coaching-counseling with the five awareness of students in maintaining its existence as a noble industry. The two strategies above illustrate that Nurul Jadid Islamic boarding school is not only central and focuses on religious education for students. However, the existence of a pesantren strategy as an Islamic educational institution that has a dual mission (studying profit and social) can make it a noble institution (nouble industry). By placing human capital and social capital as a means of meeting the needs of society and the demands of the times, Nurul Jadid Islamic Boarding School is able to improve itself, so that it is not only capable of becoming a medium for transmitting da'wah, knowledge and expertise, but also as a potential and socio-cultural interaction.